2022
DOI: 10.1016/j.pmedr.2022.101713
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 vaccine acceptance and associated factors among pregnant women in Pennsylvania 2020

Abstract: Data on factors associated with vaccine acceptance among pregnant women are critical to the rapid scale up of interventions to improve vaccine uptake. When COVID-19 vaccines were still in the testing phases of research, we surveyed pregnant women accessing prenatal care at an academic medical institution in Central Pennsylvania, United States to examine factors associated with vaccine acceptance. Willingness to receive a COVID-19 vaccine once a vaccine became available was asked as part of an ongoing study on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
(46 reference statements)
2
30
1
1
Order By: Relevance
“…Gender is known to exert significant effects on emotional processing and related emotional and behavioral consequences [ 54 , 55 ]. Gender and education are also reported to be associated with vaccine hesitancy/anxiety [ 6 , 23 , 24 , 40 , 56 ]. Being previously infected with COVID-19 is a reported predictor of vaccine hesitancy [ 24 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender is known to exert significant effects on emotional processing and related emotional and behavioral consequences [ 54 , 55 ]. Gender and education are also reported to be associated with vaccine hesitancy/anxiety [ 6 , 23 , 24 , 40 , 56 ]. Being previously infected with COVID-19 is a reported predictor of vaccine hesitancy [ 24 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant people's receipt of the influenza vaccine in the previous year and communication with a medical professional about vaccines were associated with increased likelihood of COVID-19 vaccine acceptance. 45,52,55 In contrast, pregnant people's prior refusal of the seasonal influenza vaccine, 47,54 lack of provider counseling, 50 younger age, 45,48 African American race, 47,48,50,53,54 Hispanic ethnicity, 47,48,50,54 and low education 50 were associated with refusal of vaccination. Frequently cited concerns included safety and effectiveness of COVID-19 vaccination, fears of birth defects, unknown long-term health effects on children, and risk of pregnancy loss.…”
Section: Covid-19 Vaccine Acceptancementioning
confidence: 96%
“…Vaccine hesitant pregnant people were concerned about side effects, sickness, allergy to the vaccine, and a perception that the vaccine is unnecessary. 46 A study reported 65% vaccine acceptance among pregnant people; this study had a sample consisting of people with higher education and greater income 55 in comparison to other studies. 46,47,50 The vaccine acceptance rate did not improve after the COVID-19 vaccine became available in the U.S. Studies conducted after the vaccine became available showed acceptance rates of 3%, 51 16.30%, 48 35.70%, 50 44.30%, 49 and 58.30%.…”
Section: Covid-19 Vaccine Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination also builds immunity that offers protection for the fetus or neonate against COVID-19 via passive transplacental transfer of antibodies from the immunized mother to the fetus during pregnancy or to the newborn during lactation ( 15 , 27 ). In light of the beneficial role of the vaccine for the mother, fetus, and baby with few or no adverse effects, major guidelines indicate that pregnant women are eligible for and can get any of the WHO approved COVID-19 vaccines and recommend COVID-19 vaccination during pregnancy ( 14 , 15 , 20 , 28 ). Consequently, many countries around the world, including Ethiopia, nowadays strongly advise COVID-19 vaccination for people who are pregnant, trying to get pregnant now, or might become pregnant in the future to protect them from COVID-19 ( 20 , 29 – 31 ).…”
Section: Introductionmentioning
confidence: 99%